Institutional Betrayal, Psychoanalytic Insights on the Anglican Church's Response to Abuse - Gardner, Fiona (Religions, 2022)
Psychoanalysis can advance our understanding of responses from the hierarchy of mainstream religious denominations to disclosures of abuse by clergy. This paper takes analytic insights to discuss how and why the Anglican institutional church has responded so callously to disclosures of child sexual abuse within the church. Inhumane responses have led to feelings of institutional betrayal in survivor groups. The subject is explored firstly in the context of organizational and group dynamics, and, secondly, by analysing defences that underly the interaction between the person who has been abused and the member of the church hierarchy who is hearing the disclosure. Defences and deceptions have been consciously and unconsciously used within the organization that have obstructed contact with reality, and so hindered it both in fulfilling its task in responding appropriately to what has taken place, and in adapting to changing circumstances. Churches have been active agents in re-traumatising individuals. Examples to illustrate are taken from hearings on the Anglican Church by the Independent Inquiry into Child Sexual Abuse in England, UK. The idea of organizational redemption is presented.